Duolingo-Based Arabic Vocabulary Acquisition in Islamic Educational Contexts - Kasmaluddin (Al-Muhawaroh: Jurnal Pendidikan Bahasa Arab, 2026)
This study investigates the effectiveness of Duolingo-based instruction in enhancing Arabic vocabulary acquisition within Islamic educational contexts. Employing a quantitative experimental design with a pre-test–post-test control group, the research involved forty first-grade senior students at an Islamic educational institution in Indonesia. Participants were randomly assigned to an experimental group receiving Duolingo-based vocabulary instruction and a control group taught through conventional classroom methods. Data were collected using validated vocabulary tests and supported by classroom observations and teacher field notes for triangulation. The findings reveal that students in the experimental group achieved significantly higher vocabulary gains than those in the control group, indicating that Duolingo-based learning had a strong and positive impact on Arabic vocabulary acquisition. These results suggest that gamified mobile-assisted language learning can effectively address persistent lexical challenges in Arabic education, particularly in contexts where exposure to the language is limited. The study contributes to the growing body of research on digital language pedagogy by positioning vocabulary acquisition as a central learning outcome and highlighting the pedagogical potential of Duolingo within Islamic educational settings.